Acinetobacter baumannii infection in critically ill patients with COVID-19 from Tehran, Iran: the prevalence, antimicrobial resistance patterns and molecular characteristics of isolates - Ghamari, Mahsa; Jabalameli, Fereshteh; Afhami, Shirin; Halimi, Shahnaz; Emaneini, Mohammad; Beigverdi, Reza (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe COVID-19 pandemic has led to the excessive use of antimicrobials in critically ill patients. Infections caused by Acinetobacter baumannii have increased significantly both regionally and globally during the COVID-19 pandemic, posing dramatic challenges for intensive care unit (ICU) patients. This study aimed to determine the prevalence, antimicrobial resistance patterns, presence of selected antimicrobial resistance genes, and genetic diversity of A. baumannii isolates obtained from COVID-19 cases admitted to the ICU at the University Hospital in Iran.Materials and methodsThis was a cross-sectional and single-center study comprising patients with A. baumannii infections admitted to the ICU with COVID-19 between April and November 2021. The demographic and clinical data of the patients were collected. Antimicrobial susceptibility testing was conducted based on Clinical Laboratory Standards Institute guidelines. This study used PCR and multiplex PCR to investigate antibiotic resistance genes (ARGs) and global clones (GC), respectively. Genetic diversity was investigated by repetitive element sequence-based PCR (REP-PCR).ResultsThe prevalence of A. baumannii coinfection in COVID-19 cases was 8.1% (43/528). More than 90% (39/43) of A. baumannii isolates were resistant to cefepime, ampicillin-sulbactam, gentamicin, trimethoprim-sulfamethoxazole and amikacin. Furthermore, 44.2% (19/43) of isolates were resistant to colistin. There were 91% (39/43) isolates that were extensively drug-resistant (XDR). The most prevalence carbapenem resistance encoding genes were bla-OXA-23 65.1% (29/43) and blaNDM 41.8% (18/43). The most common aminoglycoside resistance genes were aac(6’)-Ib 65.1% (28/43) and ant(2)-Ia 46.5% (20/43). Isolates from the prominent Global clone GCII comprised 83.7% (36/43) of total isolates. Genetic fingerprinting using REP-PCR revealed that 39 typeable A. baumannii isolates were categorized into 12 distinct genotypes, of which 72% (28/39) of isolates belonged to one genotype.ConclusionThe high prevalence of XDR A. baumannii such as carbapenem and colistin-resistant strains, poses a significant concern for the treatment of COVID-19 patients, heightening the risk of therapeutic failure. The data demonstrate the dissemination of a single A. baumannii clone carrying multiple ARGs within our hospital. Regarding the limited therapeutic options, it is crucial to implement effective prevention and containment policies to curb the spread of these strains.